Addition of lipolytic enzyme in anaerobic co-digestion of swine manure and inclusion levels of waste vegetable oil - Sunada, Natália da Silva [UNESP]; Lucas Júnior, Jorge de [UNESP]; Orrico, Ana Carolina Amorim; Orrico Júnior, Marco Antonio Previdelli; Schwingel, Alice Watte; Costa, Mônica Sarolli Silva de Mendonça (My University, 2014)
Studies that aim the reusing of agro-industrial wastes have become very important due to the high production of this sector and environmental preservation. The objective of this work was to evaluate the performance of digesters loaded with swine manure, increasing inclusion levels of waste oil and lipolytic enzyme, through the potential of biogas and methane production, as well as reductions in levels of total solids (TS) and volatile solids (VS). Batch digesters were loaded with substrates containing 4% TS, composed of pig manure, waste oil (ratios of 8, 10 and 12% in relation to levels of TS in the substrate) and lipolytic enzyme (0.05, 0.10, 0.15, 0.20 and 0.25% in relation to levels of TS in the substrate), water and inoculum. Maximum reduction of TS and VS were 56.13 and 64.49% respectively and occurred in inclusion levels of 0.15 and 0.13% lipase and 12% oil. The greatest potential for methane for the amounts of TS and VS added (0.23 and 0.29L) were achieved by inclusion of 12% oil and levels of 0.12 and 0.11% lipase, and these values were up to 29.7% higher than yields observed for the lowest inclusion level of enzyme. The inclusion of 12% oil and 0.15% lipase in the composition of substrates containing pig manure improves the yields of methane and reductions in pollutant constituents.
Keywords: Biodigestion; Lipase; Lipid; Methane; Swine